Pentingnya Komunikasi Efektif untuk Keberhasilan Proses Pembelajaran - Anicha Putri Catrini (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
Effective communication that occurs between educators (teachers) and students can be done by building a learning atmosphere accompanied by teacher praise for student work, accompanied by challenging teacher questions, and encouragement for students to experiment which is very important for teachers. The effect of effective and precise and varied communication plays a very important role in improving student learning outcomes. Students are more enthusiastic and motivated to express words and sentences. The use of effective communication becomes an attractive medium and can increase mastery of learning materials. Praising students' creativity must be adjusted to their character and nature. Sometimes, there are students who do not like to be praised for too long or even exhibited and sometimes there are also students who are praised for their learning motivation will be more motivated. Learning by using effective communication can be a good tool that can be used in schools. The use of effective communication media is not only at school but at home, because it can help accelerate mastery of subject matter. Students will express their ideas and thoughts freely so that they practice speaking skills and use the right language to communicate. For this reason, it is very important that an effective communication occurs between educators (teachers) and students (students) in the learning process in order to achieve successful learning.